Extracellular Vesicles as a Means of Viral Immune Evasion, CNS Invasion, and Glia-Induced Neurodegeneration - Horn, Miranda D.; MacLean, Andrew G. (Frontiers in Cellular Neuroscience, 2021)
Extracellular vesicles (EVs) are small, membrane-bound vesicles released by cells as a means of intercellular communication. EVs transfer proteins, nucleic acids, and other biologically relevant molecules from one cell to another. In the context of viral infections, EVs can also contain viruses, viral proteins, and viral nucleic acids. While there is some evidence that the inclusion of viral components within EVs may be part of the host defense, much of the research in this field supports a pro-viral role for EVs. Packaging of viruses within EVs has repeatedly been shown to protect viruses from antibody neutralization while also allowing for their integration into cells otherwise impervious to the virus. EVs also bidirectionally cross the blood-brain barrier, providing a potential route for peripheral viruses to enter the brain while exiting EVs may serve as valuable biomarkers of neurological disease burden. Within the brain, EVs can alter glial activity, increase neuroinflammation, and induce neurotoxicity. The purpose of this mini review is to summarize research related to viral manipulation of EV-mediated intercellular communication and how such manipulation may lead to infection of the central nervous system, chronic neuroinflammation and neurodegeneration.